Somatometric characteristics of children’s bodies of secondary school age with hearing impairments - Ivanytskyi, Roman; Aloshyna, Alla; Bychuk, Oleksandr (Journal of Education, Health and Sport, 2017)
The article deals with somatometric characteristics of children’s bodies of secondary school age with hearing impairments. The objective of the work is to identify and analyze somatometric indicators of children’s bodies of secondary school age with hearing impairments. The methods of the research: in order to achieve the set goal we used the method of anthropometry and methods of mathematical statistics. The results of the study showed that boys aged 11-12 years have significantly lower weight and body length than girls of the same age. At the age of 13-14 indices of body mass and body length are also lower than among the girls of the same age, but this difference is insignificant. The results of the Quetelet index show uneven change of the index of girls and boys.